Restoration of the Deskur’s House in a renewal process of Casimir Town in Radom - Gaweł, Dariusz (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
The article is a case study of the reconstruction of a tenement house located in the frontage of the town marketplatz, which is the result of revitalization works in the Casimir Town in Radom. The importance of the functional transformation and renovation of some buildings is particularly important for the success of the complex process of revitalization for the old urban districts. Therefore, the key effect of decision-making and administrative activities is the social acceptance of residents, location availability and multi-functionality of the facility. In order to confirm the initial assumptions, a quantitative survey of visitors to the facility was used. The combination of many years of activities should result in the social and cultural revival of forgotten, exploited districts with not only monumental and historic value, but also responding to contemporary social needs. In the future, long-term activities should be correlated with provisions in other operational and strategic programs in the city. This work is based on the criticism of professional literature, juxtaposed with provisions in local law documents and social research.